Key milestones in the diabetes research: A comprehensive update. (March 2020) - Gupta, Amit; Behl, Tapan; Sachdeva, Monika
Abstract: Diabetes has become a "lifestyle disease" and is growing epidemically on an alarming rate. It has become a serious socio-economic burden on the developed and under developed countries. Despite many scientific milestones achieved in proving better healthcare facilities and in the treatment and mitigation of this disease, it still imposes a serious threat in countries with middle and low-level-income group of population. Due to the gaps in diabetes prevention and treatment for management of chronic conditions associated with diabetes, there is an urgent requirement of exploring clinical pathways and therapeutic regimen to help patients in overcoming these barriers to managing their diabetes. Recent explorations in the drug discovery have opened new avenues in the development of new class of drugs which includes Amylin counterparts, Peroxisome-proliferator activated receptors targeting drugs, gastric inhibitory polypeptides analogues and dipeptidyl peptidase-4 inhibitor as newly approved potential targets. Focusing on the emerging trends and researches in the field of diabetes treatment, the review will highlight the recent scientific and technological advancements in the development of newer generation of drugs or therapeutic regimens over the past few decades. Highlights: Diabetes has emerged as a major threat to the modern word. Diabetes is responsible for a wide array of complications. Stem and gene therapy can provide benefit to the diabetic patient.